Swift/XRT view of S5 0716+714 during a flare - Wierzcholska, Alicja; Siejkowski, Hubert (Monthly notices of the Royal Astronomical Society. Letters, 2015)
Abstract. The blazar S5 0716+714 has been monitored in its flaring state between 2015 January 19 and February 22 with the Swift X-Ray Telescope (Swift/XRT). Du
Gesehen am 01.07.2020